The Influence of TikTok Media on the Knowledge of the Dangers of E-Cigarettes Among Junior High School 7 Students in Jambi City - Muhammad Raihan Octario Varid (Lembaga Pengembangan Kinerja Dosen, 2025)
E-cigarettes are now a lifestyle for teenagers in Indonesia. The popularity of e-cigarettes is increasing because many consider e-cigarettes safer to use than conventional cigarettes. With the aim of influencing tiktok media on knowledge of the dangers of e-cigarettes in SMPN 7 Jambi City students. Method: The type of research used in this study is quantiative with a quasi-experimental research design of the one group pretest-posttest type with a minimum sample of 30 with Purposive Sampling technique. The analysis used is univariate analysis and bivariate analysis with the Wilcoxon test Results: statistical tests obtained a mean difference in knowledge before (8.07) and knowledge after (16.43), so that the difference value was obtained (8.36), the results obtained (P-Value = 0.000), which shows that it has a significant increase in knowledge. Conclusion: In this study, it was found that there was an effect of increasing knowledge of the dangers of e-cigarettes in SMPN 7 students in Jambi City with Tiktok media.